Can regular follow-up imaging contribute to the determination of appropriate timing of surgery in patients with undiagnosed mucinous cystic neoplasm? A multicenter retrospective study. (2nd July 2021) - Satoh, Tatsunori; Ishiwatari, Hirotoshi; Kawaguchi, Shinya; Sato, Junya; Kaneko, Junichi; Kanemoto, Hideyuki; Sugiura, Teiichi; Sasaki, Keiko; Matsubayashi, Hiroyuki; Uesaka, Katsuhiko; Ono, Hiroyuki
Abstract: Objective: Guidelines suggest that patients with undiagnosed pancreatic cystic lesions should be monitored despite a lack of evidence supporting surveillance for undiagnosed mucinous cystic neoplasms (MCNs). We aimed to investigate the pre- and post-operative clinical course of patients with MCN and the utility of follow-up for patients who were not diagnosed with MCN at initial examination. Patients and Methods: This multicenter retrospective study enrolled 28 patients with resected pathology-proven MCN; 12 and 16 patients underwent surgery within and after 6 months from the initial examination (Groups A and B, respectively). Outcome measures included changes in imaging findings until surgery in Group B, pathological findings between both groups and differences in pathological findings between patients with and without regular follow-up imaging in Group B. Results: In Group B, the median cyst size was 30 and 48 mm at the initial examination and immediately before surgery, respectively. The incidence of mural cysts, thickened walls and mural nodules were 25, 19 and 0%, respectively, at the initial examination and 69, 56 and 31%, respectively, immediately before surgery. There were no significant differences in the invasive carcinoma rates between Groups A and B (13 vs. 17%). Regular follow-up imaging was offered to Group B. Among these, invasive carcinoma was found in one patient exhibiting no recurrence. One patient without follow-up imaging had invasive carcinoma recurrence post-operatively. Conclusions: MCNs increased in size, and typical imaging findings appeared over time. For undiagnosed MCN, regular follow-up examination contributed to the determination of the appropriate surgical timing. Abstract : Mucinous cystic neoplasms increase in size, while typical imaging findings appear over time and regular follow-up imaging would contribute to the determination of the appropriate timing of surgery.